Analisis Pengaruh Perceived Authenticity, eWOM,Price Sensitivity Terhadap Purchase Intention Di Mediasi oleh Perceived Value Pembelian Sepatu Olahraga Original di Kota Batam - Lady Lady; Ageng Ageng (Universitas Internasional Batam, 2021)
This study aims to examine the effect of Perceived Authenticity, eWOM, Price Sensitivity on Purchase Intention Mediated by Perceived Value in Purchasing Luxury Branded Sports Shoes in Batam City. Data testing was carried out by distributing questionnaires online to 356 respondents in the form of Google with the criteria of users who have bought luxury branded shoes. Data processing used non-probability sampling methods and primary data were analyzed using SPSS and Smart PLS programs. The results of this study indicate that for all variables have a significant positive effect on Purchase Intention except Perceived Value which shows a significant negative.